2003
DOI: 10.11646/zootaxa.146.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Census of “ Microturbellarians” (free-living Platyhelminthes) of the zoogeographical regions originating from Gondwana

Abstract: In this study we review microturbellarian species known to occur in zoogeographical regions that originated from Gondwana. The 510 reported species are from all types of aquatic environments (marine, brackish and freshwater). Complete data of the distribution and bibliographical references are provided. In addition, taxonomic discrepancies, as well as new combinations, are clarified. This checklist is the first revised compendium of the microturbellarians of the Gondwanian zoogeographical regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
6
0
3
Order By: Relevance
“…Curtis (1991) reported that only one species of freshwater turbellarian, Mesostoma brincki Marcus 1970, had been positively identified from Namibia. In a comprehensive global collation of turbellarian species with Gondwanan affinities, Noreña et al (2003) (Böhmig, 1914)) from the region, but did not indicate how many of these occur in temporary wetlands. Houben et al (2014) reported P. foliacea from a temporary pond in Hluhluwe Game Reserve, SA.…”
Section: Platyhelminthes (Flatworms)mentioning
confidence: 99%
“…Curtis (1991) reported that only one species of freshwater turbellarian, Mesostoma brincki Marcus 1970, had been positively identified from Namibia. In a comprehensive global collation of turbellarian species with Gondwanan affinities, Noreña et al (2003) (Böhmig, 1914)) from the region, but did not indicate how many of these occur in temporary wetlands. Houben et al (2014) reported P. foliacea from a temporary pond in Hluhluwe Game Reserve, SA.…”
Section: Platyhelminthes (Flatworms)mentioning
confidence: 99%
“…The discovery of these new species in the Pacaya-Samiria National Park in Peru suggests the existence of a high diversity of turbellarians in this area, which up to now has remained largely unknown, and increases the general knowledge of the fauna of Neotropical turbellarians (Noren˜a et al 2003). Although such a diversity has gone unnoticed, we expect it to be one of the highest in South America.…”
Section: Introductionmentioning
confidence: 97%
“…Em ambientes límnicos, os macroturbelários incluem representantes de Tricladida e os microturbelários, de Catenulida, Macrostomida, Prolecithophora, Lecithoepitheliata, Proseriata e Rhabdocela (Young 2001). Segundo Noreña et al (2003), das 510 espécies de microturbelários citadas para as regiões do Gondwana, mais de 45% foram registradas no Brasil.…”
Section: Introductionunclassified